Security Preservation in Blockchain IoT - Ajay; Kumar, Ravi; Anuradha; Anuradha (International Journal of Computer Sciences and Engineering, 2019)
With rapid development of Internet of Things (IoT) , it is evident that users get convenience in different fields such as smart homes,transportation,supply chain, smart contracts etc.Blockchain Mechanisms play a vital role in securing many IoT oriented applications.Blockchain and IoT are both intended to be world changing technologies. Merging these technologies could result in something more than the sum of its parts.IoT security using Blockchain is aimed at providing better security mechanisms so that authentication, confidentiality and integrity constraints are preserved. Based on component interaction in IoTenvironment , the security measures that are depicted in the existing work ensures that no alien commodity is allowed to tamper the data and other devices in IoT environment. However IoT devices are surprisingly insecure.Hence security issue is one of the most challenging task for utilizing Blockchain.